Measuring the Quality of Signs for Objects in the Economy - Lyudmyla Маlyarets; Oleksandr Dorokhov (Bina Nusantara University, 2017)
The problems of measuring the quality attributes for different objects in the economy were considered. This article used methods of value measuring in the economy that were determined by the existing types. In this, it must distinguish between direct primary measurement, indirect measurement, joint and combined measurement. The different ways to solve it on the basis of joint measurement of qualitative and quantitative attributes inherent to economic facilities that were explored. Stages and elements of the quantities measurement processes in the economy were classified and analyzed. The corresponding mathematical methods and tools depending on the objectives and procedures of measurements are determined. The conceptual representation of an integral quality of the object in the economy as a generalizing indicator was proposed. It finds that it is possible to make general conclusions that underestimate the role of non-metric signs in the characterization of the object that is explained by their insufficient study and poorly developed mathematical tools to measure them.